PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN MODEL PROBLEM BASED LEARNING MATERI TARI TRADISIONAL TIDI LO O’AYABU PADA SISWA KELAS VIII-B DI SMP NEGERI 7 KOTA GORONTALO - Mois, Lisna; Pulukadang, Mimy Astuty; Djafar, Nurlia; Sitharesmi, Riana Diah; Karlan, La Ode (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to describe the Differentiated learning process on Traditional Dance material using the Problem Based Learning Model for Class VIII-B Students at SMP Negeri 7 Gorontalo City. This research method is a descriptive qualitative study. The population in the study were class VIII students of SMP Negeri 7 Gorontalo City and the sample was 9 female students. The results of this study indicate that the Problem Based Learning model (group practice) for tidi lo o'ayabu can be said to be successful as seen from the evaluation of the theory of all students who have been able to master the material taught by the researcher and the evaluation of good practice is considered successful because there are only 2 out of 9 people who are not very able to demonstrate or practice tidi lo o'ayabu. The process of learning arts and culture, especially dance using the Problem Based Learning model (group practice), can improve skills and increase students' enthusiasm for learning. In addition, with this Problem Based Learning model, it can help students to support each other and work together in solving problems, if there are still some students who have not mastered the dance movements, students who are able to demonstrate the dance movements help friends who have not been able to demonstrate them properly and correctly